Effects of a Teacher-Training Program for Developing Critical-Thinking Skills in University Students of Southeast Mexico - Susana Guzmán Silva; Pedro Antonio Sánchez Escobedo (Universidad Autónoma de Baja California, 2006)
The purpose of the present study was to obtain evidence about the effect of a teacher-training program at an institution of higher education in southeastern Mexico: the University of Mayab (Unimayab). The experimental group was composed of the students of nine teachers who, during the spring semester of 2003, took a course at the Unimayab (n = 219). Nine others were invited to participate as a control group of (n = 218). At the beginning and end of the semester, participants completed the California Critical Thinking Skills Test (CCTST). The results show significant differences in the dimensions measured by this test, except for the capability for analysis. Observations of teaching practice also showed better strategies for teachers who had taken the training program. It is concluded that teacher-training can improve the development of critical-thinking skills in students. Discussed are limitations of the study, as well as the implications for teacher-training at the university undergraduate level.